Grave secrets - Cascone, Annette (Cascone, A. G. Deadtime stories., 2012)
Amanda maintains a pet cemetery in her backyard where she buries her dead pets, but when she and her friends prepare to bury a dead squirrel they find a grave with a doll in it, a discovery with links to a scary elderly neighbor.